Workhsop Penguatan Literasi Digital untuk Pelajar: Respon terhadap Era Disruptif - Akmal Sutja; Nur Hasanah Harahap; Sri Rahma Ramadhoni; Muhammad Ferdiansyah; Zubaidah Zubaidah; Rully Rully Andi Yaksa (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
The disruptive era, characterized by the acceleration of digital technology innovation, has brought profound transformations to various aspects of life, including the loss of a number of traditional jobs, the widening of the digital divide, and the emergence of ethical challenges in the use of technology. This situation is a serious concern, especially among students in Sungai Duren Village, whose parents mostly work in the agriculture and fisheries sectors, resulting in limited capacity to guide their children in dealing with digital dynamics. The goal of this community service program is to strengthen students' digital literacy through workshops designed to equip them with the skills and knowledge to address the negative impacts of digitalization, such as exposure to hoaxes, gadget addiction, and decreased social interaction. The implementation method consisted of two stages: first, interactive delivery of material through lectures, discussions, and simulations; and second, the introduction and distribution of Digital Literacy Cards as visual aids containing reflective messages to encourage a balance between digital and real life. The results of the activity showed an increase in participants' awareness and skills in sorting information, managing gadget use, and fostering creativity based on non-digital activities. This program not only improved students' digital literacy but also provided them with practical strategies to face the challenges of the disruptive era in a more critical, creative, and responsible manner.